Vacuum deposited organic and composite charge transport layers for photovoltaic devices - Klein, N (2019)
This thesis studies the mechanisms by which charge transport layers influence photovoltaic device performance. Organic hole transport layers of pentacene (Ptn) are employed in quantum dot (QD) photovoltaic devices to improve performance. Device operation mechanisms are studied through current-voltage (IV) testing, complemented by Kelvin Probe measurements of QD and Ptn layer Fermi levels. The results reveal that space-charge effects initially cause s-shaped IV curves and identify Ptn-QD energy level alignment as critical to subsequently lifting these extraction limits. Atmospheric treatments of air and nitrogen are compared, demonstrating that performance improvements stem from Ptn oxidation. Photonic UV-exposure treatments are trialled to control oxidation processes, but are not found to be effective. Overall, the studies show that Ptn performs two primary enhancement roles: electron blocking which minimises rear contact recombination, and hole extracting which balances carrier collection. A 50 nm Ptn layer gives improved performances over control devices, increasing the short circuit current (Jsc) from 9.2 to 12.9 mA/cm2. Gold (Au) and silver (Ag) nanoparticles (NPs) are added to organic layers of tris(8-hydroxyquinolinato)aluminium (Alq3) to create composite electron transport layers with modified optoelectronic properties. The NPs are characterised by AFM and UV-VIS-NIR spectroscopy, demonstrating that the evaporated metal nominal thickness controls the NP size and plasmonic absorption wavelength. The Alq3 electronic structure is altered by NP-organic interactions which create gap states and induce charge transfer. Kelvin Probe measurements of composite layers reveal that Au NPs cause larger Fermi level (Ef) shifts of 0.2 eV compared to 0.1 eV for Ag NPs. Device photocurrent changes are investigated by wavelength filtered IV testing and photoluminescence measurements. Photocurrents are found to be increased by direct NP plasmonic absorption, but reduced by NP-induced Alq3 exciton quenching. Carrier transport mechanisms are investigated through AC impedance testing, which shows NP trapping effects are outweighed by the creation of low resistance pathways. Both modified organic and direct NP pathways contribute to substantial transport improvements with increasing NP nominal thickness. The cathode metal is varied to demonstrate that interface Fermi level pinning causes extraction limits which are lifted with increasing NP nominal thickness. Au NPs induce larger interface and transport improvements at lower nominal thicknesses than Ag NPs. Composite electron transport layers, of Au NPs and Alq3, are employed in planar heterojunction organic photovoltaic devices to enhance efficiencies. The elimination of s-shaped IV characteristics with NP additions is investigated further by Kelvin Probe measurements and Mott-Schottky analysis. These studies demonstrate that Fermi level pinning at the cathode interface initially limits extraction and that NP-organic interactions cause gap state creation and filling which lifts both energy and transport related extraction limits. Comparisons to NP-only devices, without Alq3 layers, show s-shaped IV curves remain, proving that direct NP pathways are not simply circumventing extraction limits. Device absorption and EQE spectrums are measured, revealing that NP optical effects have a negligible impact on photovoltaic performance. NP electronic effects influence device carrier dynamics, which are characterised through AC impedance equivalent circuit modelling, in addition to dark and intensity dependent IV testing. NPs improve both bulk and interface transport with increasing NP nominal thickness. At high nominal thicknesses, however, these gains are outweighed by concurrent recombination increases. Both modified organic and direct NP pathways contribute to each of these mechanisms, although losses originate predominantly from direct NP effects. Devices with and without Alq3 layer are compared, showing that Alq3 enhances efficiencies by performing buffer layer roles and mitigating NP losses.